Not Three People: The Fundamental Themes of Gregory of Nyssa’s Trinitarian Theology as Seen in To Ablabius: On Not Three Gods - Ayres, Lewis (Modern theology, 2002)
Gregory of Nyssa’s small text On Not Three Gods has often been treated as a key statement of his supposedly "pluralistic" and/or "social" Trinitarianism. I argue, first, that Gregory’s intention here is to shift discussion away from a focus on the possible analogies between the divine life and three seemingly distinct human beings, toward themes more fundamental in his theology. Second, I offer a reading of On Not Three Gods to show how Gregory’s Trinitarian theology—as all pro-Nicene theologies—revolves around a strong commitment to the unity of the divine power and activity and an equally strong insistence that all statements about the divine life and persons are governed by an account of the divine incomprehensibility.